Cement Spacer versus Endoprosthesis as Reconstruction Modality after Limb Salvage for Shoulder Malignancies: Systematic Review and Meta-Analysis - Gupta, Akshat; Jalan, Divesh; Gupta, Nishith; Aggarwal, Nupur; Behera, Kshitish; Jain, Princi (Acta medica Lituanica, 2026)
Background: Limb salvage is the mainstay of surgical treatment for primary sarcomas as well as metastatic lesions of the proximal humerus. This involves wide excision of the involved humeral segment followed by a reconstruction of the defect. The purpose of this review was to determine which reconstruction modality offers a better overall functional outcome.Methods: After registering a review with the PROSPERO database (ID No. CRD 42025642215), PubMed and Cochrane Library databases were systematically screened for relevant studies meeting our inclusion criteria. The Methodological Index for Non-randomized studies (MINORs) questionnaire was the primary Risk Of Bias (ROB) assessment tool. The included articles were compared with respect to their intra-operative parameters, functional outcome scores, postoperative shoulder Range Of Motion (ROM), as well as complication rates.Results: A total of eight studies, involving 348 subjects in total, were included in this review, out of which, only four articles were found eligible for meta-analysis. Primary malignancy of the bone was the most common diagnosis (Osteogenic sarcoma followed by Ewing sarcoma). A higher frequency of axillary nerve sacrifice was seen in patients undergoing spacer implantation. Musculoskeletal Tumour Society Scores (MSTS) were used as the chief functional outcome determinant and were significantly better in patients undergoing arthroplasty (73.7+7.9 versus 68.9+8.5). A similar trend was observed with regards to shoulder flexion, extension and abduction. The most common complication noted with a cement spacer was proximal implant migration followed by implant failure. On the other hand, dislocation or subluxation of the prosthesis was the most frequently reported issue with arthroplasty. Overall, the local recurrence rate was 9.5%.Conclusion: Cement spacers are ideally suited for patients with a poor socio-economic background, aggressive lesions and a shorter life expectancy, while joint replacement is the reconstructive modality of choice in low-grade, well differentiated, isolated malignancies with negligible chances of sacrificing the shoulder abductor mechanism.
Keywords: shoulder; humerus; neoplasm; malignancy; cement spacer; arthroplasty